Effect of processed spent bleaching earth content on the compressive strength of foamed concrete - R., Othman; Khairunisa, Muthusamy; Youventharan, Duraisamy; Mohd Arif, Sulaiman (IOP Publishing, 2019)
Present research studies the effect of Processed Spent Bleaching Earth (PSBE) on the compressive strength of foamed concrete as partial replacement for cement. The mixture and specimen uses of PSBE replace cement in the proportions of 10, 20, 30 and 40 percent by weight of binder were prepared and tested. The effect of PSBE as partial cement replacement on compressive strength, flexural strength, workability, density, water absorption and carbon content of foamed concrete were reported. Results indicate that 30% PSBE significantly improved the compressive strength of foamed concrete and other properties also performed well which behaviours are comparable to normal concrete There are fewer Ca(OH)2 crystals and more CSH produces in 30% PSBE through SEM analysis is represent for its superior.